Genes and elite athletic status - Moving forward - Durmic, T. (ASPETAR Sports Medicine Journal, 2017)
Elite sport performance represents a complex phenotype, composed of various intricately intertwined biological traits, some of which are manifested at the biochemical or physiological level (state of the musculoskeletal, cardiovascular, central nervous, pulmonary or even immunological systems), while others are expressed as psychological traits (dedication, motivation, perseverance, diligence etc). Each of these traits is shaped by both environmental and genetic factors, as well as by the interaction of these factors. The relative magnitude of the effect of each of these factors on the expression of specific traits related to sport performance became a subject of debate soon after the birth of genetics as a field of scientific study, reiterated in the `born vs bred` or `nature vs nurture` discussion and summarised in the question: `are champions born or made`?